Successful Kidney Transplantation for End-Stage Renal Disease in Marfan's Syndrome - Makoto Ryosaka; Kazuya Omoto; Taiji Nozaki; Kazuhiko Yoshida; Yugo Sawada; Hajime Hirano; Tomokazu Shimizu; Hideki Ishida; Kazunari Tanabe (Case Reports in Transplantation)
Marfan’s syndrome is a systemic disorder of the connective tissue caused by mutations in the extracellular matrix protein fibrillin-1, with aortic dissection and aneurysm being its most life-threatening manifestations. Kidney transplantation for end-stage renal disease (ESRD) in patients with Marfan’s syndrome has not been reported in the literature, and the rate of the incidence of dissection or aneurysm in the iliac artery is unknown. Here, we present a patient with Marfan’s syndrome with ESRD due to severe renal ischemia caused by massive bleeding from thoracoabdominal aortic dissection leading to transplant surgery of a living kidney procured from the patient’s mother. After kidney transplantation, the renal function normalized without vascular complications, and stable graft function along with negative results for both microhematuria and proteinuria continued for two years. Also, vascular complication such as aneurysm or dissection of the iliac artery was not observed using ultrasonography during the follow-up period. ESRD patients with Marfan’s syndrome might be suitable for kidney transplantation, but long-term and careful observations are needed.